2021
DOI: 10.3390/ma14237264
|View full text |Cite
|
Sign up to set email alerts
|

Recycled Polyester Geosynthetic Influence on Improvement of Road and Railway Subgrade Bearing Capacity— Laboratory Investigations

Abstract: After years of using geosynthetics in civil engineering and infrastructure construction, it has recently become necessary to consider the possibility of recycling and reusing these materials. This paper presents the results of laboratory tests of the effect of recycled geogrid on the bearing capacity of soils using a CBR test. A polyester geosynthetic was selected for testing due to its high resistance to biodegradation and wide application. In a series of laboratory tests, two types of road and railway subgra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…These variations are considered insignificant in terms of compaction. In other words, the addition of recycled fibers does not have a significant influence on the maximum dry density and optimum moisture content values, suggesting that compaction efforts may not be significantly affected by the fiber addition [83].…”
Section: Influence Of Recycled Pet Fibers On Soil's Dry Densitymentioning
confidence: 98%
See 2 more Smart Citations
“…These variations are considered insignificant in terms of compaction. In other words, the addition of recycled fibers does not have a significant influence on the maximum dry density and optimum moisture content values, suggesting that compaction efforts may not be significantly affected by the fiber addition [83].…”
Section: Influence Of Recycled Pet Fibers On Soil's Dry Densitymentioning
confidence: 98%
“…The maximum enhancement in the CBR was observed when utilizing 4% PET strip content with the ARs of 1, 2, and 3 [128]. Malicki, Górszczyk and Dimitrovová [83] conducted a study to investigate how moisture content and the addition of recycled PET strips impact the enhancement of the CBR. The highest CBR value was attained with 11% moisture content and 2% PET strip content.…”
Section: Influence Of Recycled Pet Strips On Soil's Cbrmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, mixtures modified with rubber and polymer returned interesting results in terms of fatigue resistance [ 31 , 32 ], mechanical properties [ 33 , 34 ], and damping vibrations [ 35 ]. Moreover, geofiber reinforced soil layers have been investigated [ 36 ] and were found to obtain a cost-effective alternative to soil improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Yorulmaz et al [ 12 ] experimentally found the inclusion of an appropriate amount of waste marble powder could positively improve the bearing capacity of the subgrade soils of highly plastic silt and highly plastic clay. Malicki et al [ 13 ] presented the CBR test results of the effect of recycled geogrid on the bearing capacity of subgrade soft soils.…”
Section: Introductionmentioning
confidence: 99%